Hybrid Plasmonic Nanodumbbells Engineering for Multi-Intensified Second Near-Infrared Light Induced Photodynamic Therapy - Wang, Dong; Wang, Hongzhi; Ji, Lei; Xu, Meng; Bai, Bing; Wan, Xiaodong; Hou, Dayong; Qiao, Zeng-Ying; Wang, Hao; Zhang, Jiatao (ACS nano, 2021)
Photodynamic therapy (PDT) has shown great potential in infection treatment. However, the shallow depth of the short wavelength light and the low reactive oxygen species (ROS) production hinder its development. A strategy that can achieve a second near-infrared (NIR-II) light that is a long wavelength induced multi-intensified antibacterial PDT is most critical. Herein, hybrid plasmonic Au/CdSe x S y with precise Ag doping (ACA) nanodumbbells are rationally designed for ideal NIR-II light induced antibacterial PDT. Plasmonic Au nanorods extend the photocatalytic activity of ACA to NIR-II regions, which provides a basis for NIR-II light induced PDT. More importantly, multi-intensified PDT can be realized by the following creativities: (i) elaborate design of as-synthesized nanodumbbells that allows for electron holes to be redistributed in different regions simultaneously, (ii) the efficient hot-electrons injection that benefits from the ratio tailoring of anions ratio of Se and S, and (iii) the dopant Ag level inhibiting the combination of electron holes. The nanodumbbells create effective hot-electrons injection and a separation of electron holes, which provides great convenience for the production of ROS and allows NIR-II light induced PDT for the inhibition of bacteria and biofilms. As a result, comparably, our well-defined ACA hybrid nanodumbbells can generate about 40-fold superoxide radicals (·O2 –) and more hydroxyl radicals (·OH). Therefore, the MIC value of the as-synthesized nanodumbbells is lower than the value of 1/16 of core–shell ACA. In vivo results further demonstrate that our nanodumbbells exhibit excellent PDT efficacy.